Children, Film and Literacy - Parry, Becky; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Children, Film and Literacy examines children's engagements with film and how these engagements impact on their developing literacy, identity and textual productions.
Keywords: Social sciences; Communication; Motion pictures and television; Motion pictures -- History; Educational sociology; Education and sociology; Sociology, Educational; Social groups; Family; Youth; Childhood; Adolescence; Social Sciences; Childhood, Adolescence and Society; Film and Television Studies; Media Studies; Sociology of Familiy, Youth and Aging; Film History; Sociology of Education